Pengembangan Lembar Kerja Peserta Didik (LKPD) PJOK Senam Lantai Meroda Berbasis Penguatan Pendidikan Karakter Untuk Peserta Didik Kelas VII SMP Negeri 18 Kota Bengkulu - Muhammad Nuryogatama; Tono Sugihartono; Ari Sutisyana (Universitas Bengkulu, 2020)
Lembar Kerja Peserta Didik (LKPD), is research and development that is commonly called (R&D). The subjects of this study were Students of grade VII of SMP Negeri 18 Bengkulu City with 27 students and 2 teachers. Data analysis techniques using quantitative descriptive analysis as outlined in the form of percentages. Data collection instruments and techniques with a questionnaire. The results of the study stated that the products developed were feasible with expert validation scores, , in expert I, Content eligibility aspects